2003
DOI: 10.1210/jc.2002-021988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Parathyroid Hormone Administration on Bone Mineralization Density in Iliac Crest Biopsies from Patients with Osteoporosis: A Paired Study before and after Treatment

Abstract: Anabolic effects of PTH have been observed at several skeletal sites in humans by dual x-ray absorptiometry without differentiating between an actual increase in bone volume and an increase in mineral content within already established bone. The present study addressed this issue by evaluating the bone mineralization density distribution of iliac crest bone biopsies before and after PTH treatment for 18-36 months in men and women with osteoporosis using quantitative backscattered electron imaging. In cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
2
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(128 citation statements)
references
References 23 publications
11
112
2
3
Order By: Relevance
“…The teriparatide-induced increase in Ca Width even above normal in cancellous bone and the increase in cortical bone in this study are comparable with that reported previously in one study on patients who were naive to bisphosphonate treatment. (24) In this previous work, (24) as well as in a second study in bisphosphonate-naive patients, (25) teriparatide also decreased the average mineral content of the bone material, which was not seen in this study cohort. It is not clear whether this difference was due to the prior bisphosphonate treatment or to the shorter period of teriparatide treatment (12 months in this study versus 18 to 36 months in the previous study).…”
Section: Normal Baseline Bmdd Of Prioraln and Priorrismentioning
confidence: 46%
See 2 more Smart Citations
“…The teriparatide-induced increase in Ca Width even above normal in cancellous bone and the increase in cortical bone in this study are comparable with that reported previously in one study on patients who were naive to bisphosphonate treatment. (24) In this previous work, (24) as well as in a second study in bisphosphonate-naive patients, (25) teriparatide also decreased the average mineral content of the bone material, which was not seen in this study cohort. It is not clear whether this difference was due to the prior bisphosphonate treatment or to the shorter period of teriparatide treatment (12 months in this study versus 18 to 36 months in the previous study).…”
Section: Normal Baseline Bmdd Of Prioraln and Priorrismentioning
confidence: 46%
“…Further, larger effects on cortical BMDD have been described for osteoporotic women who continued hormone-replacement therapy during PTH treatment. (24) No differential effects of teriparatide treatment on BMDD between priorRIS versus priorALN…”
Section: Normal Baseline Bmdd Of Prioraln and Priorrismentioning
confidence: 99%
See 1 more Smart Citation
“…This could be partly explained by the fact that mineral continues to be deposited within newly formed bone during the second week of treatment without further increases in bone volume, but resulting in a significant increase in BMD. (35)(36)(37) Another possible explanation could lie in differences in osteoblast and osteoclast activity in response to PTH withdrawal. In young male rats, Gunness-Hey et al (10) reported that the PTH-stimulated osteoblast surface remained at 50% of its maximally activated status even at 12 days after PTH discontinuation, whereas the PTH-stimulated osteoclast surface returned to the control level by 8 days after discontinuation.…”
Section: Cyclic Versus Daily Pth Regimens On Mouse Bonementioning
confidence: 99%
“…PTH possesses bi-directional actions, ie, it is bone-catabolic and bone-anabolic. Many experiments have shown that continuous exposure to PTH decreases bone mass by stimulating a net increase in bone resorption, whereas intermittent administration of PTH can increase bone mass [1][2][3][4] . The mechanism involved in osteogenesis of intermittent PTH administration is not clear.…”
Section: Introductionmentioning
confidence: 99%